Impact of Fractional Flow Reserve (FFR) Guided Percutaneous Coronary Intervention (PCI) on Clinical Outcomes in Patients with Multivessel Coronary Artery Disease - Bahauddin Khan, Shah Sawar, Subtain Ul Hassan Abid, Mahmood Ul Hassan, Amir Taj Khan, Afnan Muhammad (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Coronary artery disease (CAD) is a common and serious cardiovascular condition that is characterized by the buildup of plaque in the coronary arteries. Objective: To evaluate the impact of FFR-guided PCI on clinical outcomes compared to angiography-guided PCI in patients with multivessel coronary artery disease. Methods: This was a retrospective cohort study of 200 patients with multivessel coronary artery disease who underwent PCI at Armed Forces Institute of Cardiology Rawalpindi. Patients were divided into two groups: FFR-guided PCI group (n=100) and angiography-guided PCI group (n=100). Clinical outcomes including major adverse cardiovascular events (MACE), all-cause mortality, and target vessel revascularization (TVR) were compared between the two groups. Results: The FFR-guided PCI group had a significantly lower incidence of MACE compared to the angiography-guided PCI group (5.0% vs. 17.0%, p=0.01). All-cause mortality and TVR rates were also lower in the FFR-guided PCI group, although the difference was not statistically significant. Angiographic findings showed that the FFR-guided PCI group had a significantly lower number of stents implanted per patient compared to the angiography-guided PCI group (1.3±0.6 vs. 1.8±0.7, p<0.001). Conclusion: FFR-guided PCI is associated with improved clinical outcomes compared to angiography-guided PCI in patients with multivessel coronary artery disease. The use of FFR measurement can help identify functionally significant lesions and lead to more accurate selection of lesions for revascularization. Therefore, FFR-guided PCI may be a valuable tool in the management of patients with multivessel coronary artery disease.